Correlation Analysis Between Trace Elements and Colorectal Cancer Metabolism by Integrated Serum Proteome and Metabolome - Zheng, Zhi; Wei, Qingfeng; Wan, Xianghui; Zhong, Xiaoming; Liu, Lijuan; Zeng, Jiquan; Mao, Lihua; Han, Xiaojian; Tou, Fangfang; Rao, Jun (Frontiers in Immunology, 2022)
Colorectal cancer (CRC) is the third most common cancer with a high mortality rate. However, the molecular mechanism of CRC, especially advanced CRC, remains poorly understood, resulting in few therapeutic strategies available. In order to comprehensively reveal molecular characterization of advanced CRC and the therapeutic responses, we here took advantage of data-independent acquisition (DIA)-based proteomics and ultra-performance liquid chromatography coupled to time-of-flight tandem mass spectrometry (UPLC-TOF-MS/MS) metabolomics technologies on 40 serum samples collected from 20 advanced CRC patients before and after treatment. The trace elements including Mg, Zn, and Fe were also measured by using inductively coupled plasma spectrometry (ICP-MS). General biochemical examinations and lipids measurements indicated all four CRC patients with progressive disease after treatment had impaired liver functions. On one hand, a total of 64 proteins were determined to be significantly expressed after treatment. Further analysis showed several cancer-related pathways and certain pathways participated in immune system were significantly enriched, including MAPK signaling pathway and complement & coagulation cascades. On the other hand, 128 metabolites in total were identified to be significantly changed and most of the 20 significantly enriched pathways were related to lipid metabolism. Especially, one pathway, cholesterol metabolism, was thus determined to be enriched in both the proteomic and metabolomic analyses. Moreover, the concentrations of Mg in the CRC patients were significantly lower than those in the healthy group, which returned to normal levels after treatment. Correlation analysis revealed the important roles of key lipids, proteins and Mg, specially acting immune modulators involved in the development and therapeutic mechanism of CRC. Altogether, our work not only extended our understanding on the molecular basis of advanced CRC, but provided novel therapeutic targets for the disease.